Analysis of Construction Dispute Resolution Reform Perspective of Law Number 2 of 2017 - Waisapi, Jeffry Yuliyanto (Dinasti Research, 2024)
Indonesia is pursuing development to enhance welfare through projects like office buildings, housing, and infrastructure. The involvement of societal levels is crucial for success. However, development can trigger disputes from differing interpretations or contractual provisions. This study focuses on analyzing reforms in construction dispute resolution under Law No. 2 of 2017, utilizing a quantitative survey approach. The Construction Services Acts of 1999 and 2017 marked significant shifts in philosophical outlook and dispute resolution mechanisms. Findings indicate that the 2017 Act emphasizes non-litigious settlements with a